Influence of caries risk on the retention of a resin-modified glass ionomer used as occlusal sealant: a clinical trial - Tagliaferro, Elaine Pereira Da Silva; Pardi, Vanessa; Ambrosano, Gláucia Maria Bovi; Meneghim, Marcelo De Castro; Paschoal, Marco Aurelio Benini; Cordeiro, Rita De Cássia Loiola; Pereira, Antonio Carlos (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
AbstractIntroduction Little is known whether caries risk influence occlusal sealants retention.Objective To determine the retention rates (RR) of the resin-modified glass ionomer cement used as occlusal sealant in permanent first molars of 6-8-year old schoolchildren and to analyze the influence of caries risk at baseline on the RR of the sealant, over a 24-month period.Material and method The sealant application was performed in a dental office at the beginning of the study, after children being allocated into high caries risk group (HR) and low caries risk group (LR). The examinations were performed by the same calibrated dentist at 0, 6, 12, 18 and 24 months. Retention rates were estimated, the Kaplan-Meier method was used to estimate the survival probabilities; and the comparison between HR and LR groups was evaluated by Wilcoxon and log-rank test.Result The results showed that 14% of sealed teeth showed total loss (16% for HR and 12% for LR) and 46% showed partial loss during the study (51% for HR and 41% for LR), in relation to the baseline sample. No difference could be demonstrated by the survival analysis between HR and LR groups (p>0.05).Conclusion Caries risk did not influence the retention rates of a resin-modified glass ionomer cement used as occlusal sealant in 6-8-year old schoolchildren.

ResumoIntrodução Pouco se sabe sobre a influência do risco de cárie na retenção de selantes oclusais.Objetivo Avaliar as taxas de retenção de um cimento de ionômero de vidro modificado por resina utilizado como selante oclusal em primeiros molares permanentes de escolares de 6-8 anos, e analisar a influência do risco de cárie na taxa de retenção do selante, durante um período de 24 meses.Material e método A aplicação do selante foi realizada em consultório odontológico no início do estudo, após as crianças serem alocados no grupo de alto risco (AR) ou baixo risco (BR) de cárie. Os exames foram realizados pelo mesmo dentista calibrado em 0, 6, 12, 18 e 24 meses. As taxas de retenção foram estimadas e o método de Kaplan-Meier foi utilizado para estimar as probabilidades de sobrevivência. A comparação entre os grupos AR e BR foi avaliada pelos testes de Wilcoxon e log-rank.Resultado Os resultados mostraram que 14% dos dentes selados apresentaram perda total (16% para AR e 12% para BR) e 46% apresentaram perda parcial durante o estudo (51% de AR e 41% para BR), em relação a amostra no início do estudo. Nenhuma diferença pode ser demonstrada pela análise de sobrevivência entre os grupos AR e BR (p> 0,05).Conclusão O risco de cárie não influenciou as taxas de retenção de um cimento de ionômero de vidro modificado por resina usado como selante oclusal em escolares de 6-8 anos de idade.
Influência do risco de cárie na retenção de um ionômero de vidro modificado por resina usado como selante oclusal: ensaio clínico
Keywords: Schoolchildren; caries; risk; survival analysis; Escolares; cárie; risco; análise de sobrevivência